Kinematics of bicruciate and posterior stabilized total knee arthroplasty during deep knee flexion and stair climbing. Issue 6 (25th June 2020) - Ishibashi, Teruya; Tomita, Tetsuya; Yamazaki, Takaharu; Tsuji, Shigeyoshi; Yoshikawa, Hideki; Sugamoto, Kazuomi
Abstract: Second‐generation bicruciate stabilized (BCS) total knee arthroplasty (TKA) was developed to substitute both anterior and posterior cruciate ligaments and replicate physiological kinematics. This study aimed to evaluate if the postcam mechanism and the surface geometry function effectively. Seventeen and twelve knees implanted with BCS TKA and posterior stabilized (PS) TKA, respectively, were analyzed. In vivo kinematics during deep knee flexion were estimated from single‐plane fluoroscopic images using a 2‐dimensional to 3‐dimensional image registration technique. Flexion angle, anteroposterior translation, femoral external rotation (ER), and postcam engagement were compared between the groups. Postoperative 2011 Knee Society Score (KSS) was obtained at the last follow‐up. The medial femoral condyle in BCS was positioned more anteriorly than that in PS from minimum flexion to maximum flexion. Posterior motion of the lateral femoral condyle was observed in both groups. ER of BCS was significantly larger compared to PS from minimum flexion to 100°. However, the amount of ER from minimum flexion to maximum flexion was similar: 6.2° ± 4.5° and 7.7° ± 4.1° in BCS and PS, respectively ( P  = .364). Anterior postcam engagement was observed in 76.5% and 25.0% in BCS and PS, respectively ( P  = .006). Posterior postcam engagement was observed in all cases in BCS and PS. There were no significant differences in KSS between the groups. The kinematic differences were likely a result of variations in articular surface geometry.